The effect of supportive care plan on anxiety in patients with acute coronary syndrome after admission to CCU - Leila Alikhah; Mohsen Koushan; Moosaalreza Tadayonfar; Rahim Akrami; Narjes Heshmatifar; Sedighe Rastaghi (Tehran University of Medical Sciences, 2019)
Background & Aim: Many patients with cardiovascular disease suffer from some degree of anxiety after admission to the Cardiac Care Unit (CCU). Anxiety adversely affects patients' recovery. High levels of anxiety increases mortality risk up to three times. This study aimed to determine the effect of pre-operative supportive care plan on anxiety of patients with acute coronary syndrome after admission to CCU. Methods & Materials: In this clinical trial, 74 patients with acute coronary syndrome, admitted to the Cardiac Care Unit of Vasei hospital of Sabzevar in 2016. Participants were selected via convenience sampling and randomly divided into two groups of intervention and control. The control group only received routine nursing care. For the intervention group, besides routine care, the supportive nursing care was delivered on the intellectual, emotional and physical domains. The Beck Anxiety Inventory questionnaire was completed by both groups before and after the intervention. The data were analyzed by the Mann-Whitney U test and independent t-test using the SPSS software version 16. Results: Before the intervention, no significant difference was observed in the anxiety score between the intervention and control groups (P=0.162). After the intervention, the anxiety score in the intervention group was lower than in the control group (P=0.023). Conclusion: According to the results of this study, supportive care plan reduced anxiety in the intervention group compared to the control group. Therefore, supportive care plan is recommended for reducing anxiety in these patients. Clinical trial registry: IRCT2015123025767N1